The Analysis of Local Own Revenue and Grant Expenditures on Regional Expenditures of Central Kalimantan Province - Dedy Heronaldo Thamus (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the effect of local revenue and grant spending on regional spending in Central Kalimantan Province. The research object is the Regional Finance and Asset Agency and the Regional Revenue Agencyregarding the Regional Budget (APBD) of Central Kalimantan Province taken from 2015-2019. Research data is secondary data. The sampling method used was convenience sampling.The novelty in this research is an imitation of previous research with some updating of data and variables. The test method in this study uses multiple linear regression, the results show: (a) local revenue has an effect on regional spending, (b) grant spending has no effect on regional expenditure, (c)regional revenue and grant expenditure have a simultaneous effect on spending area.